Glucopuncture: A Clinical Guide to Regional Glucose 5% Injections - Jan Kersschot (Glucopuncture: A Clinical Guide to Regional Glucose 5% Injections, 2023)
Glucopuncture (GP) is a treatment modality with an interesting risk-benefit ratio. GP is defined as the clinical application of isotonic sugar water (ISW) injections such as glucose 5% or dextrose 5%. Other products such as local anesthetics or steroids are not added. Each session, multiple injections are applied into soft tissues such as dermis, muscles and ligaments. The goal of GP is to modulate pain and to support tissue repair. GP can be applied for nonrheumatic musculoskeletal pain, sports injuries and regional neuropathic pain. In acute situations, one or two sessions will be effective but in chronic cases a series of sessions is required. The dose of sugar water is so low that it can be used for patients with diabetes. This book describes the mode of action and clinical application of GP in a variety of medical conditions. This book is an invitation for further basic-science and randomized clinical studies to clarify the potential benefits of regional ISW injections for musculoskeletal pain.